Large scale deletion and rebalancing within the k1C kafirin family in sorghum - Ferris, Tyler W.; Hurst, Preston J.; Yobi, Abou; Alartouri, Bara; Li, Aixia; Angelovici, Ruthie; Clemente, Thomas E.; Holding, David R. (Frontiers in Plant Science, 2025)
Sorghum bicolor (L.) Moench (sorghum) is cultivated as food for humans and livestock and is valued for its low input requirements. However, sorghum grain protein is deficient in the essential amino acid lysine and has poor protein digestibility. This is because highly abundant proline-rich kafirins constitute >70% of proteins and form low-digestibility protein bodies. To reduce kafirin expression in the endosperm and elicit wholesale proteome rebalancing to increase non-kafirin proteins, a single guide RNA (sgRNA) Clustered Regularly Interspaced Short Palindromic Repeats (CRISPR/Cas9) construct was previously used to target members of the highly repetitive alpha-kafirin family, k1C, in RTx430 sorghum. The current study was conceived to evaluate the nutritional and biophysical characteristics of two sorghum lines with k1C family deletions compared to unedited RTx430. Despite confirming a ~400-kb deletion in the k1C family of both edited lines encompassing seven active genes, no significant decrease was observed in k1C expression or compensatory increase in non-kafirin proteins. A significant increase was observed in protein-bound amino acids in both k1C-deleted lines and in both edited lines relative to unedited RTx430, which increased total seed protein in one line. Protein bodies were observed to be more irregularly shaped, with seeds retaining wild-type levels of vitreous endosperm. RNA Isoform Sequencing (Iso-Seq) was performed to measure k1C family gene expression and capture differentially expressed non-kafirin genes. Five k1C members were observed to have biologically significant expression, with only two of the residual, non-deleted k1C genes having elevated expression in lines with the deletion. The results of this study demonstrate the ability of CRISPR/Cas9 editing of kafirins to elicit changes to the amino acid profile of sorghum and increase protein. Moreover, the results demonstrate an extreme example of the ability of highly repetitive genome regions such as the k1C subfamily to compensate for the effects of CRISPR-induced multigene deletions.